Psychiatry training in 42 European countries: a comparative analysis - Baessler, Franziska; Zafar, Ali; Gargot, Thomas; Pinto da Costa, Mariana; Biskup, Ewelina Maria; De Picker, Livia; Koelkebeck, Katja; Riese, Florian; Ryland, Howard; Kazakova, Olga; Birkle, Sarah; Kanellopoulos, Thanos; et al. (European neuropsychopharmacology, 2021)
Psychiatry qualifications are automatically recognized among European Union (EU) countries despite differences in national training programs. A widening gap between the number of psychiatrists, their competencies and the growing burden of mental illnesses in Europe has renewed calls for international standardization of training. Comprehensive information about training programs is missing, which limits thorough comparisons and undermines development of an actionable strategy to improve and harmonize psychiatry training. This study describes and compares the existing postgraduate psychiatry programs in 42 countries in the European region. Representatives of national psychiatry associations completed a semi-structured, 58-item questionnaire. Training structure and working conditions of each country were compared with population needs calculated by the World Health Organization to determine the European mean and contrasted among pre-2004 and post-2004 EU members and countries with unrecognized qualifications. Differences were tested with nonparametric (Wilcoxon) and parametric (Anova) tests. Median training duration was 60 months, significantly shorter in countries with unrecognized qualifications (48 months, χ²16.5, p < 0.001). In 80% of the countries, placement in a non-psychiatric specialty such as neurology or internal medicine was mandatory. Only 17 countries (40%) stipulated a one-month rotation in substance abuse and 11 (26%) in old-age psychiatry. The overall deficit of training versus population need was 22% for substance abuse and 15% for old-age psychiatry. Salaries were significantly higher in pre-2004 EU members (χ²22.9, p < 0.001) with the highest in Switzerland (€5,000). Significant variations in curricula, training structure and salaries exist in Europe. Harmonization of training standards could offer significant benefits for improving mental healthcare.
Gesehen am 14.07.2021